Residual effect of vermicompost and preceding groundnut on soil fertility and associated Striga density under sorghum cropping in Eastern Ethiopia. - Addisu F Ebbisa; Nigussie Dechassa; Zelalem Bekeko; Feyera Liben (PLoS ONE)
Depletion of soil organic matter was found to be the primary biophysical factor causing declining per capita food production in sub-Saharan Africa. The magnitude of this problem was exacerbated by moisture-stress and imbalanced fertilizer application that caused Striga weed infestation. To address such confounded issues, two-year field experiments were conducted to evaluate the effect of residual vermicompost and preceding groundnut on soil fertility, sorghum yield, and Striga density. The first-year treatments contained two sowing methods (single and intercropped sorghum), two seedbed types (open-furrow and tied-ridge), and four vermicompost rates (0, 1.5, 3.0, and 4.5 t/ha) combined factorially in a randomized block design. In the second-year experiment, only monocropped sorghum with seedbed types was sown exactly on the same plot as the previous year's treatment combinations without fertilizer. The results disclosed that residual vermicompost at 4.5 t/ha in intercropped sorghum/groundnut significantly reduced soil pH (0.76%), bulk density (8.61%), electrical conductivity (38.78%), and Striga density (85.71%). In contrast, compared to unamended soil, the aforementioned treatment combined with tied-ridging increased soil moisture, organic matter, and sorghum yield by 16.67, 2.34, and 58%, respectively. Moreover, this treatment combination markedly increased post-harvest soil organic carbon (7.69%), total N (0.247%), available P (38.46%), exchangeable-Fe (27%), and exchangeable-Zn (40%) in the second year over control. Treatments previously amended with 4.5 t/ha of vermicompost under the sorghum-groundnut intercrop system resulted in the highest total N (0.242%) and available P (9.822 mg/Kg). Thus, the vermicompost and groundnut successfully improve soil fertility and sorghum yield for two cropping seasons.